2002
DOI: 10.1071/ar01197
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between weaning age, weaning weight, sex, and enzyme supplementation on growth performance of pigs

Abstract: Digestive capacity of early-weaned pigs may be insufficient to fully digest many ingredients currently used in weaner diets. The aim of this experiment was to determine whether an exogenous enzyme preparation with broad carbohydrase activity could benefit pigs that developmentally might be immature at weaning, especially with regard to gastrointestinal development. Eighty Large White × Landrace pigs were used in a 2 × 2 × 2 × 2 factorial experiment with the factors being: weaning age (14 or 24 days), weaning w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…In the current study, the activities of trypsin, amylase, colipase, and lipase were expressed per gram of pancreas in order to standardise enzyme measurements, because pancreatic weights were influenced by all factors in the study except gender (Table 3). Increased trypsin activity in pigs weaned at 28 days of age and in heavier pigs might partly explain why these pigs perform better after weaning than pigs weaned at 14 days of age or which are light-for-age (Dunshea et al 2003a). There was no increase in the specific activity of amylase after weaning; however, Cranwell et al (1997) showed an increase in the total activity of amylase in the pancreas with time after weaning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the current study, the activities of trypsin, amylase, colipase, and lipase were expressed per gram of pancreas in order to standardise enzyme measurements, because pancreatic weights were influenced by all factors in the study except gender (Table 3). Increased trypsin activity in pigs weaned at 28 days of age and in heavier pigs might partly explain why these pigs perform better after weaning than pigs weaned at 14 days of age or which are light-for-age (Dunshea et al 2003a). There was no increase in the specific activity of amylase after weaning; however, Cranwell et al (1997) showed an increase in the total activity of amylase in the pancreas with time after weaning.…”
Section: Discussionmentioning
confidence: 99%
“…at 14 days of age. This most likely reflected the greater level of voluntary feed intake seen in pigs weaned at an older age (Dunshea et al 2002(Dunshea et al , 2003b. Cranwell (1995) summarised data from numerous studies highlighting the rapid growth of gastrointestinal organs after weaning, and concluded that the weaned pig requires a relatively larger digestive system than a sucking pig to satisfactorily digest and absorb the inherently less digestible diets offered after weaning, and maintain a commercially acceptable level of performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Growth rates may be different in early weaned piglets compared with those with a more prolonged lactation period (Dunshea et al, 2002;Sharon et al, 2003;Main et al, 2004), and intestinal development in piglets late weaned may be more advanced (Callesen et al, 2007;Wellock et al, 2007). This situation has been described extensively in the literature that compared different weaning ages, and in most of them, late weaning showed better results than early weaning.…”
Section: Resultsmentioning
confidence: 99%
“…This situation should not pose major problems as long as the growing pig has the ability to digest, absorb, and use the nutrients provided in its new diet. Nevertheless, piglets have a reduction in absorption capacity after weaning, and weaning age can markedly affect the ability of weaned piglets to adapt to the dietary changes associated with weaning (Dunshea et al, 2002;Sharon et al, 2003;Main et al, 2004;Callesen et al, 2007;Wellock et al, 2007).…”
Section: Introductionmentioning
confidence: 99%